Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Kopi Kenangan Pada Cabang Cilincing Landak Jakarta Utara - Achmad Maulana; Ai Netty Sumidartiny (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This study aims to determine the extent to which price and product quality influence consumer purchasing decisions at Kopi Kenangan, Cilincing Landak branch, North Jakarta. Using a descriptive quantitative method and questionnaires distributed to 100 respondents, the data were analyzed through validity and reliability tests, multiple linear regression, and hypothesis testing using SPSS. The results show that both price and product quality have a positive and significant influence on purchasing decisions. Consumers consider price affordability and product quality aspects such as reliability and durability. It is recommended that the company maintain a balance between price and quality to sustain consumer interest amid market competition. Keywords: Import Ban Policy, Policy Impact, Second-Hand Clothing, Tangerang City, Thirft Business